The Financial Interrelationship: Are Oil and U.S. Dollar Affecting Gold Market? - BOUSSALEM, Abu-Bakr (Milev Journal of Research and Studies, 2015)
The precious metal gold has been used as money for many centuries till the breakdown of the “Breeton Woods” agreement. In addition to its use as jewelry and electrical components, gold is now used as an asset investment and a hedging strategy against inflation, this leads us to consider the gold market as a financial market .The price of gold has known small changes over the period: 1833 to 1973 (before the breakdown of Breeton Woods agreement) ,from 20,65 per ounce in 1833 to 42 per ounce in 1971.After 1973 , gold has fluctuated , it was about 384 per ounce in 1982 and 283 per ounce in 1999. The gold price has risen dramatically since 2001 from its low level of 250 per ounce, then it reached a peak in 2011 with a level of 1700 per ounce. The main objective of this paper is to focus on the gold market and try to analyze empirically the trend of gold price and the causes behind its fluctuations. The paper provides first the literature review highlighting the factors that affect the gold price and its trend. Second, using a Multivariate-GARCH model, we search for the effect of the different economic indicators on the movements of the gold price and if they are a real cause beyond its volatility. Finally, a concluding section is provided to compare the results with the existent literature.